Disappearing Destinations: Climate Change and Future Challenges for Coastal Tourism - Jones, Andrew (CABI, 2014)
The growth of coastal tourism destinations and their relationship with the coastal environments in which they are located have become current and sometimes controversial topics of research, that are increasingly discussed internationally. In this respect, coastal destinations, beaches and beach resorts have become synonymous with tourism, tourism growth and economic success. With current predictions of climate change and sea level rise they are, however, becoming increasingly threatened by climate induced damage and economic uncertainty. In this context a fairly recent report by the UK-based Churchill Insurance Group highlighted that some of the world’s most famous tourist attractions, such as Australia’s Great Barrier Reef and Italy’s Amalﬁ coast, could be closed to visitors within a few years because of worries about environmental damage and climate change. The report suggested that some destinations could be permanently closed to tourists by 2020 or face severe restrictions on visitor numbers and sharp increases in access costs. The report forecasted clear warnings, that within 20 to 40 years, destinations such as the Great Barrier Reef, Islands of the Carib- bean, Paciﬁ c and Indian Ocean and swathes of America’s Gulf Coast and Europe’s Mediterranean Basin could experience severe damage, in turn forcing the closure or economic demise of many coastal tourism destinations.